The Effect of Promotion, Price, and Product Quality on Purchase Decisions Marketplace Shopee Users - I Dewa Gede Aditya Satria Wibawa; Kiromim Baroroh; Alifia Putri Rahmadani (International Journal Business, Management and Innovation Review, 2025)
This study aims to determine: (1) the effect of Promotion on the Purchase Decision of Shopee Marketplace Users, (2) the effect of Price on the Purchase Decision of Shopee Marketplace Users, (3) the effect of Product Quality on Purchase Decisions of Shopee Marketplace Users, (4) the effect of Promotion, Price, and Product Quality on Purchase Decisions of Shopee Marketplace Users. This research is a quantitative research. The respondents to this study were 100 students of the Accounting Education Study Program, Faculty of Economics, Yogyakarta State University, class of 2019 and 2020. The sampling technique used purposive sampling. Data collection techniques used questionnaires and were analyzed using Spearman's rank test and Kendall-W test. The results of the study show that: (1) Promotion has a positive and significant effect on the Purchase Decision of Shopee .Marketplace Users. This can be seen from the correlation coefficient value of 0.735 and a significance value of 0.000 <0.05. (2) Prices have a positive and significant effect on the Shopee Marketplace Purchase Decision. This can be seen from the correlation coefficient value of 0.647 and a significance value of 0.000 <0.05. (3) Product quality has a positive and significant effect on the Shopee Marketplace Purchase Decision. This can be seen from the correlation coefficient value of 0.666 and a significance value of 0.000 <0.05. (4) Promotion, Price, and Product Quality have a positive and significant effect on the Shopee Marketplace Purchase Decision. This can be seen from the W value of 0.796, the value of Xcount > Xtable (238,940 > 123,225), and the significance value of 0.000 <0.05.